Food and housing insecurity and homelessness among students in an open-enrollment university*. Issue 1 (2nd January 2020) - Trawver, Kathi R.; Hedwig, Travis
ABSTRACT: This paper reports on survey findings assessing the extent of food and housing insecurity and homelessness at an open enrollment institution of higher learning in the U.S. A random sample of 3000 degree-seeking students were e-mailed a link to an electronic survey with assistance and institutional support from the Office of Student Affairs. A total of 193 students completed a survey. Over 44% reported experiencing some type of food insecurity and more than 30% reported being unsure of their ability to pay rent. In the current study, 8.3% of students had experienced homelessness since beginning college. Results showed that food and housing insecurity and homelessness were a reality on the study site campus. As a result, greater awareness has developed surrounding college students' vulnerabilities to food and housing insecurity and homelessness and efforts are underway to identify ways to best support students through degree completion and beyond.